Narvacan Beach Resort Complex - Cadaoas, Allan V. (Manila : National University, 2000)
Beach resort complex is a combination of shore of water, that have or provides recreational facilities and entertainment, hotels and cottages to accommodate local and foreign tourists.
Title page -- Letter of endorsement -- Jury's Approval sheet -- Acknowledgement -- Dedication -- Chapter I. Introduction -- Chapter II. Methodology -- Chapter III. Terms of references -- Chapter IV. Design framework -- Chapter V. Design Analysis and presentation -- Chapter VI. Conclusion and recommendation.
Includes bibliographical references.
Keywords: BEACH RESORT -- PLANNING; BEACH HOTEL -- PLANNING